Musical Electroacupuncture May Be a Better Choice than Electroacupuncture in a Mouse Model of Alzheimer’s Disease - Jing Jiang; Gang Liu; Suhua Shi; Zhigang Li (Neural Plasticity)
Objectives. To compare musical electroacupuncture and electroacupuncture in a mouse model of Alzheimer’s disease. Methods. In this study, 7.5-month-old male senescence-accelerated mouse prone 8 (SAMP8) mice were used as an Alzheimer’s disease animal model. In the normal control paradigm, 7.5-month-old male SAMR1 mice were used as the blank control group (N group). After 15 days of treatment, using Morris water maze test, micro-PET, and immunohistochemistry, the differences among the musical electroacupuncture (MEA), electroacupuncture (EA), Alzheimer’s disease (AD), and normal (N) groups were assessed. Results. The Morris water maze test, micro-PET, and immunohistochemistry revealed that MEA and EA therapies could improve spatial learning and memory ability, glucose metabolism level in the brain, and Aβ amyloid content in the frontal lobe, compared with the AD group (P<0.05). Moreover, MEA therapy performed better than EA treatment in decreasing amyloid-beta levels in the frontal lobe of mice with AD. Conclusion. MEA therapy may be superior to EA in treating Alzheimer’s disease as demonstrated in SAMP8 mice.